Learners in the Metaverse: A Systematic Review on the Use of Roblox in Learning - Jining Han; Geping Liu; Yuxin Gao (MDPI AG, 2023)
The development of the Metaverse has drawn much attention in education. Roblox, as an important platform in the Metaverse, attracts millions of young users, which raises the question of how its effectiveness as a learning environment can be maximized. This study aims to synthesize the available evidence to provide an overview of the current research on learning in Roblox by exploring its benefits, challenges, and existing gaps. In line with PRISMA and assisted by LDA topic modeling, we included 40 studies that were analyzed to answer our questions. The research findings show that: (1) Roblox could be combined with social interactive learning or collaborative learning environments, provide a VR environment that supports learning, and be of benefit to programming in STEM education; (2) the use of Roblox in learning has the advantages of attracting a large number of student users, eliciting the positive attitudes of students, and promoting students' cognitive and noncognitive learning abilities; and (3) there are also challenges such as cyberbullying, cybersecurity, lack of adequate teaching design, etc. Empirical studies on this topic have only begun to emerge, and more future research is needed into different pedagogical scenarios to explore the effects, factors, outcomes, designs, etc.